Palliative care and teacher knowledge: possible dialogues in the health area (Research, Society and Development, 2022)
The purpose of this article is to present the knowledge and feelings of professors in addressing themes related to palliative care such as: finitude, death and grief in the undergraduate medical course at the University of São Caetano do Sul. A quantitative and exploratory cross-sectional study was carried out, carried out from the precepts and stages of the scientific method, with the application of a semi-structured questionnaire, through Googleforms, to professors of the medical graduation course. The methodological instrument used was a 17-question questionnaire investigating personal, professional and PC information. The sample consisted of 106 participants. Based on the results, we observed that about a third of the professors do not have training in the area of palliative care. Considering the issues of death and mourning, less than 50% of professors had this knowledge at graduation. The survey also revealed that approximately 88% of professors talk to students about death safely, in contrast to the literature in which many physicians feel fearful when dealing with death and palliative care, because they are misinterpreted. It is hoped with this research that the results can be effectively known by faculty of medicine, who act with more sensitivity to the needs of the population and the individual, and consequently share with students a more humanized approach.